TWO NEW PERUVIAN SPECIES OF BEGONIA (BEGONIACEAE) AND AN AMENDED DESCRIPTION OF BEGONIA THYRSOIDEA - Moonlight, P. W.; Tebbitt, M. C. (Edinburgh Journal of Botany, 2016)
Begonia speculum is described and illustrated as a new species endemic to the San Martín Region of Peru, and compared with Begonia cremnophila Tebbitt and Begonia lutea L.B.Sm. & B.G.Schub. Begonia erythrothrix is described and illustrated as a new species endemic to the Cuzco Region of Peru, and compared with an updated description of Begonia thyrsoidea Irmsch., which is lectotypified. Using International Union for Conservation of Nature criteria, Begonia speculum is considered Vulnerable; B. erythrothrix and B. thyrsoidea are assessed as Data Deficient.